2006
DOI: 10.1093/jac/dkl223
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in non-typhoidal Salmonella from human sources, Spain, 2001-2003

Abstract: The results of our study showed both a worrying percentage of strains of Salmonella Enteritidis resistant to nalidixic acid and of strains of Salmonella Typhimurium with a pattern of resistance to four antibiotics or more. Surveillance of antimicrobial resistance should carry on and improve in order to be able to evaluate the control measures carried out for decreasing resistance in Salmonella, specifically that addressed to the prudent use of antimicrobial agents by farmers and veterinarians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 15 publications
4
11
0
7
Order By: Relevance
“…The resistance rates to ampicillin and chloramphenicol were also higher in S. Typhimurium. This serotype had the highest resistance rates in the world, and the antimicrobial resistance rates in the present study were similar to those found in other countries (12,(22)(23)(24). S. Enteritidis also had higher resistance rates to ampicillin, chloramphenicol, cefotaxime, and TMX.…”
Section: Discussionsupporting
confidence: 89%
“…The resistance rates to ampicillin and chloramphenicol were also higher in S. Typhimurium. This serotype had the highest resistance rates in the world, and the antimicrobial resistance rates in the present study were similar to those found in other countries (12,(22)(23)(24). S. Enteritidis also had higher resistance rates to ampicillin, chloramphenicol, cefotaxime, and TMX.…”
Section: Discussionsupporting
confidence: 89%
“…PT 21 has been detected in isolate from humans and poultry products between 1995 and 1997 (Nunes et al, 2003). Whereas PT1 is the most prevalent PT in Italy (Nastasi et al, 1997), Denmark (Baggesen et al, 1997), Finland (Lukinmaa et al, 2006), Spain (Soler et al, 2006), and Japan (Itagaki et al, 2004).…”
Section: Pfge and Ptmentioning
confidence: 99%
“…Others studies supposed that the widespread use of antimicrobials in veterinary medicine may contribute to increase the resistance of pathogens to humans. Furthermore, the diversification of phage types results is probably associated with bacteria acquiring phage restricting plasmids or temperate phages (9,12). The emergence of phage types associated to multidrug resistance is a potential public health risk due to the zoonotic nature of human salmonelosis.…”
Section: Discussionmentioning
confidence: 99%